A Cyborg on Clouds Field (Palíndromo, 2015)
This article presents the figure of cyborg as adequate to deal with the current state of mutual incorporation between organic and synthetic. The understanding of this condition contributes to the acquisition parameters for viewing interaction mechanisms that promote hybridization of technical objects with the human and the demar- cation of the relevance of his understanding for the analysis of relations between subject, interfaces and complex communication systems. Through the crossing of ideas developed by Derrik de Kerckhove, Lucia San- taella, Bruno Latour, Vilém Flusser, Caroline Jones, Donna Haraway and Gilbert Somon- don, we have built a path from language as a first aggregate technical apparatus to the human until the polyphony of voices found in characters virtual.
Keywords: Cyborg; hybrids; technical objects; interaction